Thermo-gaseous-mechanical coupling phase-field model for brittle crack propagation in tungsten - Yuanyuan Wang; Xinxin Hou; Yan-Dong Wang (Journal of Materials Research and Technology)
Modeling of crack deflection/penetration as intergranular/transgranular fracture in the polycrystal under the coupled thermo-gaseous-mechanical multi-physics field has long been a challenge for both fracture mechanics and materials science. The current developed model builds upon a coupled mechanics, gas diffusion and temperature gradient, driven by minimizing the energy function. The time-dependent variables are solved in an implicit integration framework, where displacement, gas concentration, temperature and damage variable are the primary ones. The proposed fracture model is particularly appropriate for capturing the change of crack path in nuclear-grade tungsten (W) on account of temperature- and gas-dependent mechanical parameters. The significant contributions are three-fold: (1) the Young's modulus, Poisson's ratio and fracture energy at the given temperature and gas concentration can be automatically identified; (2) the transformation mode related to the angle between grain boundary (GB) axis and loading direction and the misorientation between two adjacent grains is predicted in the absence and presence of gas; (3) the comparative analysis of crack characteristics under constant temperature and temperature gradient is conducted with a focus on crack growth rate and crack path. The model is validated by comparing our simulated data with available experimental and numerical results. This work could have profound implications for evaluating the catastrophic failure in the extreme environment and providing guidance on optimizing the microstructure of W.